Impacts of high-altitude aerosol hygroscopicity on cloud microphysics in the North China Plain: A WRF fast-SBM modeling study - Qian Gao; Hui He; Xiang'e Liu; Yan Yang; Rong Yuan; Ping Tian; Kai Bi; Fei Wang; Jiujiang Sheng; Yongqing Wang (Atmospheric Research, 2026)

Efficient purification of bio-oil-derived levoglucosenone via a multi-stage synergistic separation strategy - Kai Li; Yong-sheng Ma; Bo Wang; Ding-wang Qiao; Qi Niu; Cheng-long Ruan; Bi-heng Bao; Xin-hua Yuan; Qiang Lu (Biomass and Bioenergy, 2026)

Glycocalyx-mimetic ionotronic silk films for immunoregulatory infected wound repair and wearable motion sensing - Zi-Xian Dang; Ke Ma; Han Zhang; Chun-Ning Bi; Yu-Ting Li; Ke-Zheng Chen; Sheng-Lin Qiao; Yong-Tao Zhang (Chemical Engineering Journal, 2026)

Condensate-boosted SOD/CAT-mimetic nanozyme reactivity for antioxidant therapy of wear particle-induced periprosthetic osteolysis - Han Zhang; Ke Ma; Zi-Xian Dang; Chun-Ning Bi; Yu-Ting Li; Ke-Zheng Chen; Sheng-Lin Qiao; Yong-Tao Zhang (Chemical Engineering Journal, 2026)

TRIM9-Mediated Degradation of SMAD4 Promotes Pyroptosis and Disruption of the Endothelial Barrier in Aortic Dissection Disease - Hong-Qin Bi; Tan Yang; Sheng-Lin Ling; Feng-Xu Yu (Cardiovascular Toxicology, 2026)

Effect of explicit intermediate layer on the solution accuracy of the thermal stress for printed circuit heat exchangers with the homogenization method - Xiaoxu Zhang; Zirui Xu; Enhui Li; Yin Tan; Jiyuan Bi; Dan Zheng; Sheng Wang; Ting Ma (Annals of Nuclear Energy, 2026)

Rhizosphere fungal communities and glomalin-related soil proteins underlie divergent drought responses in indica and japonica rice - Sihan ZHOU; Yanhan JI; Junguo BI; Jiaxuan XU; Jingrui QIU; Xiaoqin ZENG; Zixian JIA; Zijin BIAN; Ning LING; Shuai ZHAO; Sheng ZHOU; Lijun LUO; et al. (Pedosphere, 2026)

Block-structured thermoplastic polycarbonate-based polyurethane films for perovskite solar cells: Enabling low-temperature encapsulation, high barrier properties, and tunable mechanical properties - Yuting Ouyang; Zihan Zhao; Min Xiao; Dongmei Han; Sheng Huang; Dongqin Bi; Shuanjin Wang; Yuezhong Meng (Chemical Engineering Journal, 2026)

Invasions of alien plants pose unprecedented challenges to China’s nature reserves under climate change - Jia-Xin Wang; Rainer W. Bussmann; Fei Qin; Yun-Fen Liang; Bao-Cai Han; Hai-Yan Bi; Tian-Tian Xue; Sheng-Xiang Yu (Biodiversity and Conservation, 2026)

Exploring molecular-level rolling friction based on cyclodextrins for lubrication - Jiao Wang; Hao Cao; Wei You; Ding Xiao; Lan Sheng; Yuan Wang; Honggang Mei; Qing Bi; Xuedong Xiao; Yuping Wang; Guangfeng Li; Chenchen Wang; et al. (Carbohydrate Polymers, 2026)

Morphology - seepage - stress coupling response of fractured rock mass MICP reinforcement under confining pressure: in-situ NMR reveals roughness threshold effect - Yongle Liu; Jing Bi; Lin Ning; Sheng Ren; Ziyang Zhao (Bulletin of Engineering Geology and the Environment, 2026)

Synergistic electrocatalytic-biological degradation of Ni-EDTA in a baffled three-dimensional reactor: Performance optimization and mechanism analysis - Huihui Sheng; Yan Feng; Xinqiang Jia; Xinwei Wang; Yuyu Lu; Jingran Bi; Yanzhen Yu (Journal of Cleaner Production, 2026)

Biosynthesis of active small molecule prenylsalidroside a and its anti-inflammatory activity - Jia-Hao Xue; Hua-Jin Yu; Long-Jun Li; Gui-Hu Lu; Pei-Shan Li; Xia Cheng; Qi Luo; Wei Wu; Zhong-Sheng Bi (Natural Product Research, 2026)

Dissolved and particulate phosphorus turnover in a river dominated marginal sea traced by cosmogenic 32P and 33P - Cheng Xu; Bin Yang; Jinlong Wang; Sheng Zeng; QianQian Bi; Jinzhou Du (Water Research, 2026)

Resource utilization of spent grains, an underutilized by-product from Chinese Baijiu brewing: Recent advances and prospects - Zhao Yang; Sheng Wang; Bi Chen; Fan Yang; Ping Xiang; Li Wang; Jianlong Wang (Resources, Conservation and Recycling, 2026)

Promoting aerobic denitrification in the rhizosphere by vertical spatial stress: A strategy to enhance nitrogen conversion efficiency in constructed wetlands - Sheng-Jing Zhang; Hao-Qi Lu; Lei Yang; Li-De Wang; Bi-Han Zhang; Chao-Wen Deng; Jun Lan; Yong-Xiang Ren (Environmental Research, 2026)

Recovery mechanisms of deteriorated nitrogen removal in aerobic granular sludge with/without salinity stress: Enhanced nitrification and transformed denitrification pathways - Zihan Sheng; Jie Xu; Shichang Liu; Yuan Gao; Xuejun Bi; Shujuan Huang; Dong Chen; Lin Li (Environmental Research, 2026)

Mussel protein-graphene hybrid sponge with lung-mimicking architecture for rapid glucose detection - Haohao Shi; Nan Sun; Qikun Li; Dongchen Tan; Sheng Bi; Linguang Li; Shuai Yang; Chengming Jiang (Chemical Engineering Journal, 2026)

Enhanced microalgal-bacterial granulation via a novel two-stage strategy: initial Microthrix parvicella-induced limited filamentous bulking and subsequent hydrodynamic-phototrophic synergy - Mengting Li; Zhipeng Chen; Zhaoming He; Sheng Yu; Weican Shi; Qian Bi; Xiang Li; Jiaqi Hu; Shuang Qiu; Shijian Ge (Bioresource Technology, 2026)

Calcium-loaded activated carbon microtubes as a structural framework of aerobic granules: crosslinking networks overcome native framework limitations - Jie Xu; Yuan Gao; Zihan Sheng; Xuejun Bi; Shujuan Huang; How Yong Ng (Water Research, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Genome-Wide Identification and Expression Analysis of β-Ketoacyl-CoA Synthase Family in Sugarcane (Saccharum spontaneum) - An-zi Li; Xin Peng; Yuan Huang; Zhao-fu Bi; Ming-jing Liao; Mu-qing Zhang; Sheng-hua Xiao (Tropical Plant Biology, 2025)

RAGE deficiency ameliorates abdominal aortic aneurysm progression - Cong Bi; Bingqi Liu; Peixian Gao; Chuanle Wang; Sheng Fang; Zhengkun Huo; Qingpeng Song; Dianning Dong; Xuejun Wu; Gang Li (Inflammation Research, 2025)

Biosynthetic rule-guided theoretical chemical space mapping strategy for enhanced analysis of plant metabolomes: application to the geographical profiling of goji berry - Wan-Yang Sun; Zhi-Hui Luo; Jie-Qi Cai; Qian Guo; Guo-Tao Chen; Guo-Dong Chen; Dan Hu; Hai-Guang Gong; Xue Li; Wei Bi; Ying Wang; Kwok-Fai So; et al. (Science Bulletin, 2025)

Sesamol inhibits fungal growth by destroying the redox dynamic equilibrium in Pestalotiopsis neglecta - Jing-Yu Ji; Li-Ying Huang; Bing Bi; Ya-Jun Wang; Jin-Yan Zhao; Sheng-Yu Zhang; Ze Wang; Shu-ming Cui; Qiao-ya Zhang; Guo-Cai Zhang (Physiological and Molecular Plant Pathology, 2025)

Thermally triggered tunable-thermal-conductivity phase-change composites for lithium-ion battery thermal management and runaway mitigation - Tianyi Li; Junxiu Piao; Dongliang Xu; Yuhui Meng; Lifu Zhang; Xu Han; Xiaoran Yang; Linze Jin; Sheng Bi (Chemical Engineering Journal, 2025)

Forms of chitin-polysaccharide cross-linking in the Coprinopsis cinerea stipe cell wall - Baiyun Duan; Jingjing Bi; Zhonghua Liu; Yiting Zhu; Zhenqing Zhang; Lei Sun; Liqin Kang; Bin Wu; Wenming Zhang; Sheng Yuan (Carbohydrate Polymers, 2025)

Wet deposition fluxes of cosmogenic 32P, 33P and its utility in tracing air mass mixing in coast of east China sea - Cheng Xu; Sheng Zeng; QianQian Bi; Gi-Hoon Hong; Jinzhou Du (Atmospheric Environment, 2025)

Prediction of shear characteristics at core pile-cemented soil interface for offshore wind turbine pile foundation based on machine learning - Yu-liang Yan; Yu-xi Zeng; Yong-chao Liu; Bing-bing Li; Xiu-feng Liu; Bi-sheng Xu (Ocean Engineering, 2025)

A matrix for estimating the unfrozen water content of freezing soils - Jun Bi; Guoxu Wang; Wenxuan Mu; Haiyan Wen; Wansheng Pei; Qiyong Zhang; Sheng Yang; Mengyao Mao; Gaochao Lin; Chong Wang (CATENA, 2025)

Exploring mechanisms of radiation-induced myocardial fibrosis using HMGB1 neutralizing antibody - Gang Wang; Bi-Bo Wu; Sha-Sha Zhao; Jing Zhang; Yu Wang; Yin-Xiang Hu; Jun Wan; Bing Lu; Sheng-Fa Su (Journal of Molecular Histology, 2025)

The mechanism and optimization of secondary droplet fragmentation in the liquid–liquid cyclone reactor for ionic liquid alkylation - Jinghe Bi; Fuguo Wang; Xinhao Li; Fajian Li; Xiaogang Xu; Sheng Chen; Liyun Zhu; Zhenbo Wang (Chemical Engineering Journal, 2025)

Ripening-stage variations in small metabolites across six banana cultivars: A metabolomic perspective - Huijun Gao; Ping Liu; Weidi He; Fangcheng Bi; Chunhua Hu; Guiming Deng; Tongxin Dou; Qiaosong Yang; Chunyu Li; Ganjun Yi; Ou Sheng; Tao Dong (Food Chemistry, 2025)

Membrane-associated NAC transcription factor MaNAC169 is a positive regulator during banana fruit ripening - Fan Liu; Xueli Sun; Jia He; Jingjing Shan; Ou Sheng; Tongxin Dou; Yaoyao Li; Weidi He; Qiaosong Yang; Chunhua Hu; Huijun Gao; Xinxiang Peng; et al. (Postharvest Biology and Technology, 2025)

Activation of Centromedial Amygdala GABAergic Neurons Produces Hypotension in Mice - Xiaoyi Wang; Ziteng Yue; Luo Shi; Wei He; Liuqi Shao; Yuhang Liu; Jinye Zhang; Shangyu Bi; Tianjiao Deng; Fang Yuan; Sheng Wang (Neuroscience Bulletin, 2025)

Revealing the key organelle in the pathophysiology and clinical applications of animal toxins: Mitochondria - Linfeng Wang; Jiahao Liu; Sheng Zhou; Jiaqi Sun; Meiling Liu; Jianqi Zhao; Lixia Cheng; Zejing Wen; Xiaowen Bi; Chunhong Huang (Toxicon, 2025)

Implications of the different submerged extent of typical sandbars to local DOM and SDOM during the pre-flood season in the middle reaches of Yangtze River - Haoyang Shi; Hui Guo; Wenjun Yang; Chengcheng Bao; Xinxin Zhu; Sheng Bi; Yu Hu; Ting Li (Journal of Environmental Management, 2025)

Functional divergence of CAD-like family genes in Saccharum complex under biotic and abiotic stress - Zhu-Qing Wang; Sheng-Ren Sun; Hao-Yu Wang; Zheng-Wang Bi; Hai-Long Chang; Shuo-Hang Zhang; Jun-Lv Chen; Yuan-Xia Qin; Jian-Tao Wu; Wei Zhang; Huan-Ying Xu; San-Ji Gao; et al. (Plant Cell Reports, 2025)

Mechanism of Lung Fibrosis Caused by Rare Earth Samarium Oxide Through Hippo Signaling Pathway and the Intervention of GBE - Ruixia Ding; Ying Sun; Teng Ma; Haijing Yin; Yannan Bi; Sheng Li; Li Wang; Xiaohui Wang (Biological Trace Element Research, 2025)

Regulatory Roles and Therapeutic Potential of miR-122-5p in Hypoxic-Ischemic Brain Injury: Comprehensive Review - Abdulaziz S. Bamahel; Xun Sun; Wei Wu; Chenxi Mu; Jia Liu; Sheng Bi; Hui Xu (Cell Biochemistry and Biophysics, 2025)

Hyperconnectivity and Connectome Gradient Dysfunction of Cerebello-Thalamo-Cortical Circuitry in Alzheimer’s Disease Spectrum Disorders - Chenyang Yao; Yi Shan; Bixiao Cui; Zhigeng Chen; Sheng Bi; Tao Wang; Shaozhen Yan; Jie Lu (The Cerebellum, 2025)

Retraction notice to “Green economic recovery in central Asia by utilizing natural resources” [Resour. Pol. 83 (2023) 103621] - Zengrong Li; Yanqiu Wu; Ehsan Rasoulinezhad; Yishen Sheng; Chunyu Bi (Resources Policy, 2025)

Preparation and characterization of microcrystalline cellulose/corn starch-based active packaging enhanced by resveratrol/β-cyclodextrin complex - Na Yang; Haojie Sha; Wenlu Bi; Sheng Li; Shusong Wu; Dingding Su (Food Packaging and Shelf Life, 2025)

Paper-like foldable shape memory wood actuator with consecutive gesture programming by water and thermal dual stimuli for soft robots - Linze Jin; Xu Han; Junxiu Piao; Yuhui Meng; Xiaoran Yang; Lifu Zhang; Zitian Zhang; Chengming Jiang; Sheng Bi (Chemical Engineering Journal, 2025)

Predicting the volumetric heat capacity of freezing soils using the soil freezing characteristic curve - Jun Bi; Yuxuan Pan; Sheng Yang; Renwei Li; Zhijian Wu (Journal of Hydrology, 2024)

MoS2/ZnS heterostructure cathode with intralayer regulation for eco-friendly, degradable zinc-ion batteries - Fengfeng Li; Hongwei Sheng; Yifeng Qi; Wenxiang Wang; Zhaopeng Wang; Huasheng Bi; Lingxiao Ma; Daicao Wan; Haoshuo Zhang; Yuqi Ma; Jiao Yuan; Wenquan Li; et al. (Chemical Engineering Journal, 2024)

A new method to estimate the soil freezing characteristic curve - Jun Bi; Chaozheng Shen; Guoxu Wang; Zhijian Wu; Sheng Yang; Jianguo Lu; Gaochao Lin (Cold Regions Science and Technology, 2024)

Dynamic evolution of particulate and gaseous emissions for typical residential coal combustion - Siyuan Li; Dantong Liu; Xiaotong Jiang; Ping Tian; JiuJiang Sheng; Yangzhou Wu; Kang Hu; Kai Bi; Ruijie Li; Delong Zhao; Mengyu Huang; Shaofei Kong; et al. (Science of The Total Environment, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Smartphone-assisted mobile fluorescence sensor for self-calibrated detection of anthrax biomarker, Cu2+, and cysteine in food analysis - Sheng Wang; Jun Xu; Fengzhi Yue; Lina Zhang; Ning Bi; Jian Gou; Yongxin Li; Yuanyuan Huang; Tongqian Zhao; Lei Jia (Food Chemistry, 2024)

Characterization, antioxidant and α-amylase inhibition of polysaccharides and phosphorylated derivatives from finger citron (Citrus medica L. var. sarcodactylis Swingle) - Feilin Wang; Huizhong Hu; Yufu Li; Jinhong Zhong; Haihui Pan; Yuanhao Sheng; Yongguang Bi; Fansheng Kong (Food Bioscience, 2024)

Achieving near-unity quantum yield in blue ZnSeTe quantum dots through NH4F molecular-assisted synthesis for highly efficient light-emitting diodes - Lijuan He; Sheng Cao; Qiuyan Li; Yuhe Bi; Yusheng Song; Wenyu Ji; Bingsuo Zou; Jialong Zhao (Chemical Engineering Journal, 2024)

Lightweight, ultra-broadband SiOC-based triply periodic minimal surface meta-structures for electromagnetic absorption - Junbin Lu; Mingming Sheng; Hongyu Gong; Jie Jing; Xiaobin Zhou; Jianqiang Bi; Weibin Zhang; Guifang Han; Zidong Zhang; Haoyu Fang; Yijie Zhou; Ke Bi (Chemical Engineering Journal, 2024)

Anti-epileptic and Neuroprotective Effects of Ultra-low Dose NADPH Oxidase Inhibitor Dextromethorphan on Kainic Acid-induced Chronic Temporal Lobe Epilepsy in Rats - Jing-Jing Yang; Ying-Xin Liu; Yan-Fang Wang; Bi-Ying Ge; Ying Wang; Qing-Shan Wang; Sheng Li; Jian-Jie Zhang; Ling-Ling Jin; Jau-Shyong Hong; Sheng-Ming Yin; Jie Zhao (Neuroscience Bulletin, 2024)

The effect of microgroove pattern modification combined with MOF coating on titanium alloy for the soft tissue integration of percutaneous implants - Baobao Xue; Sheng Miao; Yue Yuan; Wenbo Geng; Donglin Li; Chao Yang; Jiahao Zeng; Kaiyong Cai; Hongbo Wei; Long Bi; Junjun Fan (Chemical Engineering Journal, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Crosstalk between methanogens and methanotrophs determines methane emissions in a rice paddy under different watering regimes - Xianxian Zhang; Zuopeng Lv; Huifeng Sun; Junguo Bi; Jining Zhang; Cong Wang; Sheng Zhou (Applied Soil Ecology, 2024)

Characterization, bioactivity, sustained release capacity and digestive stability of acidic sugarcane leaf polysaccharide liposomes - Fengyu Jiang; Feilin Wang; Yuanhao Sheng; Haihui Pan; Weiming Chen; Yongguang Bi; Fansheng Kong (Food Bioscience, 2024)

Effect of human chorionic gonadotrophin (HCG) and luteinizing hormone releasing hormone A3 (LHRH-A3) on reproduction and development of brood pouch in Hippocampus erectus - Xuange Liu; Gongpei Wang; Jiahui Chen; Sheng Bi; Chenlei Huang; Han Lai; Huadong Yi; Haiyang Li; Qiuxian Chen; Li Lin; Zhilun Zhang; Xuchong Wei; et al. (Aquaculture, 2024)

LuF3: Yb3+/Tm3+@Lu6O5F8: Yb3+/Tm3+@BiOI for efficient degradation of pollutants under NIR light: Synergy of enhanced upconversion emission and efficient FRET - Mengjiao Sheng; Juanqin Xue; Guangdong Wu; Yujie Liu; Qiang Bi (Journal of Environmental Chemical Engineering, 2023)

p-Nrf2/HO-1 Pathway Involved in Methamphetamine-induced Executive Dysfunction through Endoplasmic Reticulum Stress and Apoptosis in the Dorsal Striatum - Tao Wei; Jun-Da Li; Yu-Jing Wang; Wei Zhao; Fan Duan; Yan Wang; Ling-Ling Xia; Zhao-Bin Jiang; Xun Song; Yu-Qiong Zhu; Wen-Yi Shao; Ze Wang; et al. (Neurotoxicity Research, 2023)

RETRACTED: Green economic recovery in central Asia by utilizing natural resources - Zengrong Li; Yanqiu Wu; Ehsan Rasoulinezhad; Yishen Sheng; Chunyu Bi (Resources Policy, 2023)

The Study of Fishing Vessel Behavior Identification Based on AIS Data: A Case Study of the East China Sea - Bowen Xing; Liang Zhang; Zhenchong Liu; Hengjiang Sheng; Fujia Bi; Jingxiang Xu (Journal of Marine Science and Engineering, 2023)
The goal of this paper is to strengthen the supervision of fishing behavior in the East China Sea and effectively ensure the sustainable development of fishery resources. Based on AIS data, this paper analyzes three types of fishing boats (purse seine operation, gill net operation and trawl operation) and uses the cubic spline interpolation algorithm to optimize the ship trajectory and construct high-dimensional features. It proposes a new coding method for fishing boat trajectory sequences. This method uses the Geohash algorithm to divide the East China Sea into grids and generate corresponding numbers. Then, the ship trajectory is mapped to the grid, the fishing boat trajectory points are associated with the divided grid, and the ship trajectory ID is extracted from the corresponding grid. The extracted complete trajectory sequence passes through the CBOW (continuous bag of words) model, and the correlation of trajectory points is fully learned. Finally, the fishing boat trajectory is converted from coordinate sequence to trajectory vector, and the processed trajectory sequence is trained by the LightGBM algorithm. In order to obtain the optimal classification effect, the optimal superparameter combination is selected. We put forward a LightGBM algorithm based on the Bayesian optimization algorithm, and obtained the classification results of three kinds of fishing boats. The final result was evaluated using the F1_score. Experimental results show that the F1_score trained with the proposed trajectory vectorization method is the highest, with a training accuracy of 0.925. Compared to XgBoost and CatBoost, the F1_score increased by 1.8% and 1.2%, respectively. The results show that this algorithm demonstrates strong applicability and effectiveness in fishery area evaluations and is significant for strengthening fishery resource management.

Genome-wide transcriptome analysis uncovers gene networks regulating fruit quality and volatile compounds in mango cultivar 'Tainong' during postharvest - Li Li; Ping Yi; Jian Sun; Jie Tang; Guoming Liu; Jinfeng Bi; Jianwen Teng; Meijiao Hu; Fang Yuan; Xuemei He; Jinfeng Sheng; Ming Xin; et al. (Food Research International, 2023)

Acanthopagrus latus migration patterns and habitat use in Wanshan Islands, Pearl River Estuary, determined using otolith microchemical analysis - Guanglong Tang; Zehua He; Yong Liu; Yayuan Xiao; Sheng Bi; Ye Sun; Jiman Liang; Peng Wu; Teng Wang; Jinyu Ye; Chunhou Li (Frontiers in Marine Science, 2023)
Introduction The waters surrounding the Wanshan Islands are important traditional fishing grounds in China, with rich habitat types. Acanthopagrus latus is an economically important species in this area; however, the distribution of its spawning grounds and habitat use patterns remain unknown. Methods Thus 100 otolith samples of A. latus were collected from three geographic areas (MW: Qi’ao Island Mangrove Water Habitat; OW: Yamen Estuary Oyster Farm Water Habitat; RW: Dong’ao-Guishan Island Reef Water Habitat), and the concentrations of Sr and Ca along the shortest axis of the vertical otolith annual or lunar rings were measured to span the entire life cycle of A. latus , with the core and edge areas corresponding to environmental characteristics at birth and capture, respectively. Results and discussion Analysis of covariance (ANCOVA) revealed that the ratios of Sr/Ca in otolith edges of RW samples are significantly higher than those of OW and MW samples; however, both the values of Sr/Ca ratio in otolith cores collected from OW and MW are comparable with those of RW samples. Cluster analysis and non-metric multidimensional scaling (nMDS) indicated that at the juvenile stage, RW and MW individuals in the two main clusters belonged to the same cluster. There was no significant difference between the cores of the RW samples and the edges of the MW and OW samples. Therefore, the spawning area of A. latus in the Wanshan Islands is thought to have originated from low to medium-salinity waters with mangroves and oyster farm habitats in the Pearl River Estuary. A. latus from RW was found to have three distinct habitat-use patterns: 1) Marine Resident (7.2% of sampled fish) fish that remain in marine habitats for life; 2) Marine Migrant (16.4% of sampled fish) juveniles inhabit low to moderate salinity habitats and migrate to marine habitats as they grow; 3) Estuarine Visitor (76.4% of sampled fish) repeated migration between low to moderate salinity and marine habitats. This suggests widespread migration between estuarine and marine habitats throughout the ontogeny. The plasticity of this habitat use and the protection of spawning grounds should be considered in future fisheries management because A. Latus in this area has been the victim of the overexploitation of resources.

Hydrostatic pressure shock induced diploid/tetraploid mosaic in mandarin fish (Siniperca chuatsi), with the observation of embryo development and change in body spots - Zhilun Zhang; Huadong Yi; Yuqin Su; Chenlei Huang; Xuchong Wei; Qiuxian Chen; Jiahui Chen; Haiyang Li; Sheng Bi; Han Lai; Xuange Liu; Shuang Liu; et al. (Aquaculture, 2023)

Optimizing embankment structures in a snowy permafrost region of the pan-Arctic based on a coupled numerical model - Sheng Yang; Mingyi Zhang; Jun Bi; Wansheng Pei; Ruiqiang Bai (Transportation Geotechnics, 2023)

Expanded polytetrafluoroethylene/poly(3-hydroxybutyrate) (ePTFE/PHB) triboelectric nanogenerators and their potential applications as self-powered and sensing vascular grafts - Dongfang Wang; Chen Wang; Zhaojie Bi; Baokai Zhou; Lixia Wang; Qian Li; Lih-Sheng Turng (Chemical Engineering Journal, 2023)

Sedimentary record of climate change in a high latitude fjord—Kongsfjord - Hang Wu; Binbin Deng; Jinlong Wang; Sheng Zeng; Juan Du; Peng Yu; Qianqian Bi; Jinzhou Du (Acta Oceanologica Sinica, 2023)

Mitigation of low temperature stress by increased salinity is associated with multiple physiological responses in the gills of Takifugu fasciatus - Sisi Ma; Sheng Luo; Kai Zhang; Yuxi Liu; Xiaozhen Wei; Jinghao Cheng; Yihui Bi; Yiru Sun; Xinyu Zhang; Shaowu Yin; Tao Wang (Marine Biology, 2022)

RNA-Seq Reveals the Effect of Ethylene on the Volatile Organic Components (VOCs) of Cavendish Banana at Different Post-harvesting Stages - Tongxin Dou; Chunhua Hu; Shujing Zhao; Huijun Gao; Weidi He; Guiming Deng; Ou Sheng; Fangcheng Bi; Qiaosong Yang; Chunyu Li; Ganjun Yi; Tao Dong (Journal of Plant Growth Regulation, 2022)
Aroma serves as one of the decisive factors influencing the value of banana commodities. Most of characteristic volatile organic components (VOCs) are formed during post-harvesting. However, the changing of VOCs of banana at different post-harvesting stages remain ambiguous. In this study, the VOCs of Cavendish banana for the four typical post-harvesting stages (green stage/half of yellow stage/yellow ripening stage/over ripening stage) are clarified using headspace solid phase micro-extraction (HS-SPME), combined with gas chromatography-mass spectrometry (GC–MS). The results inferred that the relative content of branched-chain esters such as acetate and butyrate, which form the main contributors of aroma in bananas, is higher in the T2 and T3 stages. Further, RNA-Seq technology was employed to clarify the formation mechanism of banana aroma in the post-harvesting stage. The MaTGL4 gene of the linoleic acid metabolism pathway and the MaBCAT3 and MaBCAT5 genes of the valine, leucine and isoleucine degradation pathway in banana suggest the expression is active late in the ripening stage, and the upregulated expression of these genes is analogous to the formation of aroma components such as branched-chain esters and hexenal. The above results not only provide baseline data on the differences in physical and chemical properties of VOCs in various post-harvesting stages of banana production, but also provide theoretical guidance facilitating the subsequent improvement of the commercial value of bananas through genetic improvement.

Tea consumption and cerebral hemorrhage risk: a meta-analysis - Pengfei Cheng; Junxiang Zhang; Wenting Liu; Quan Sun; Zhaoxin Fu; Hao Lin; Sheng Bi; Jiaying Zhu (Acta Neurologica Belgica, 2022)

Development and Validation of a Diagnostic Nomogram to Predict the Anthracycline-Induced Early Cardiotoxicity in Children with Hematological Tumors - Zhi-yuan Liu; Yun-gong Wang; Xiao-bi Huang; Xiao-hui Qi; Cui-ping Qian; Sheng Zhao (Cardiovascular Toxicology, 2022)
This study aimed to establish and validate an effective nomogram to predict the risk of cardiotoxicity in children after each anthracycline treatment. According to the inclusion and exclusion criteria, the eligible children were randomly divided into the training cohort (75%) and the validation cohort (25%). Least absolute shrinkage and selection operator (LASSO) regression was used to select the predictors and a nomogram was developed. Then, concordance index ( C -index), the area under the curve (AUC), Hosmer–Lemeshow (H–L) test, and decision curve analysis (DCA) were employed to evaluate the performance and clinical utility of nomogram. Internal validation was processed to inspect the stability of the model. A total of 796 eligible children were included in this study and divided into a training set ( n = 597) and a validation set ( n = 199). LASSO regression analysis revealed that cumulative anthracycline dose, ejection fractions, NT-proBNP, and diastolic dysfunction were effective predictors of cardiotoxicity. The nomogram was established based on these variables. The C -index and the AUC of the predicting nomogram were 0.818 in the training cohort and 0.773 in the validation cohort, suggesting that the nomogram had good discrimination. The calibration curve of the nomogram presented no significant deviation from the reference line, and the P -value of the H–L test was 0.283, implying a preferable degree of calibration. The threshold of DCA also reflects that the nomogram is clinically useful. A nomogram was developed to predict anthracycline chemotherapy-induced cardiotoxicity in children with hematological tumors. The nomogram has a good prediction effect and can provide a reference for clinicians’ diagnosis and treatment.

Species and Functional Dynamics of the Demersal Fish Community and Responses to Disturbances in the Pearl River Estuary - Zeyu Zeng; William W. L. Cheung; Han Lai; Huadong Yi; Sheng Bi; Haiyang Li; Xiaoli Chen; Yuqin Su; Xuange Liu; Qiuxian Chen; Zhilun Zhang; Xuchong Wei; et al. (Frontiers in Marine Science, 2022)
Fishery resources are threatened by environmental changes and anthropogenic pressures, particularly in coastal ecosystems. It is crucial to understand the changes of fish communities and their responses to environmental changes and human disturbances to formulate rational fisheries and ecosystem-based management. The Pearl River Estuary (PRE) is a typical sub-tropic coastal ecosystem located in the center of the Guangdong-Hong Kong-Macao Greater Bay Area in the northern South China Sea. The demersal fish in the PRE is traditionally targeted as commercial fishing and severely impacted by overexploitation and hypoxia in the last few decades. In this study, we analyze the fish survey data during the period of 2020~2021 using multivariate statistics to investigate the impacts of human disturbances on the species and functional dynamics of the demersal fish community in the PRE. The results reveal that dissolved oxygen and temperature have significant correlations with the functional traits of the demersal fish community. The impacts of hypoxia on the demersal fish vary with species and locations. We found that the mean functional redundancy of the demersal fish community in the PRE was high across three surveys, but the functional diversity was low in this region. The abundance and richness of the demersal fish community increased during the summer fishing moratorium in the South China Sea in 2021, but the functional diversity did not increase significantly. We conclude that the high functional redundancy in the PRE might not be sufficient to buffer against environmental disturbances because of its low functional diversity. Our study highlights the complicated interactions between the demersal fish community and disturbances in the PRE. Understanding the traits structure and functional diversity of the fish community can help elucidate the factors determining the dynamic responses of the fish community to disturbances.

Identification and statistical characteristics of foreshock sequences in the North–South seismic belt - Jin-Meng Bi; Chang-Sheng Jiang (Journal of Seismology, 2022)

Cassiterite oxygen isotopes in magmatic-hydrothermal systems: in situ microanalysis, fractionation factor, and applications - Yang Li; Sheng He; Rong-Qing Zhang; Xian-Wu Bi; Lian-Jun Feng; Guo-Qiang Tang; Wen-Zhong Wang; Fang Huang; Xian-Hua Li (Mineralium Deposita, 2022)

Estimate greenhouse gas emissions from water-saving and drought-resistance rice paddies by deNitrification-deComposition model - Xianxian Zhang; Huifeng Sun; Junguo Bi; Bo Yang; Jining Zhang; Cong Wang; Sheng Zhou (Clean Technologies and Environmental Policy, 2022)

Proper deficit irrigation applied at various stages of growth can maintain yield and improve the comprehensive fruit quality and economic return of table grapes grown in greenhouses * - Xuelian Jiang; Binggang Liu; Xueqiang Guan; Ziqiang Wang; Baojie Wang; Sheng Zhao; Yunpeng Song; Yueling Zhao; Junlai Bi (Irrigation and Drainage, 2021)
In order to investigate the quantitative response of yield, fruit quality and economic return of table grapes grown in greenhouses under deficit irrigation applied at various growth stages, experiments were conducted in 2017 and 2018. Three irrigation levels (full irrigation, 2/3 and 1/3‐full irrigation) were applied at the fruit setting–swelling (stage 2), veraison (stage 4) and whole growth stages. The comprehensive fruit quality index ( Q c ) was determined in order to evaluate the overall quality of the berries and its effect on economic return. The results showed that deficit irrigation significantly decreased evapotranspiration (ET) and yield, and improved water use efficiency (WUE), individual quality parameters and Q c . Fruit quality was more sensitive to water deficit at stage 4 than at stage 2. Significant linear functions were found between a relative decrease in yield, berry quality parameters, Q c and a relative seasonal ET deficit. Net income under deficit irrigation was related to the price proportional coefficient ( R ). Higher net income was mainly determined by a higher yield when R was less than 1, while higher net income was determined by a higher Q c when R was greater than 3. An appropriate water deficit level at stages 2 and 4 (F 2/3 V 2/3 ) is recommended as an optimal treatment as it produces a higher Q c , the highest WUE and net income without a significant decrease in yield.

Satellite‐derived NDVI underestimates the advancement of alpine vegetation growth over the past three decades - Hao Wang; Huiying Liu; Ni Huang; Jian Bi; Xuanlong Ma; Zhiyuan Ma; Zijian Shangguan; Hongfang Zhao; Qisheng Feng; Tiangang Liang; Guangmin Cao; Bernhard Schmid; et al. (Ecology, 2021)
Satellite‐derived normalized difference vegetation index (NDVI) data are increasingly relied on to reveal the growth responses of vegetation to climate change, yet the vegetation growth tracking accuracy of these data remains unclear due to a lack of long‐term field data. Here, we adopted a unique field‐measured seasonal aboveground biomass dataset from 1982–2014 to assess the potential of using satellite‐derived NDVI data to match field data in regard to the interannual variability in seasonal vegetation growth in a Tibetan alpine grassland. We revealed that Global Inventory Monitoring and Modeling System (GIMMS) NDVI data captured the advancement of field‐measured vegetation growth throughout the entire study period but not from 2000–2014, while MODIS NDVI data still observed this advancing trend after 2000 to a limited extent. However, satellite‐derived NDVI data consistently underestimated the advancement degree of field‐measured vegetation growth, regardless of whether GIMMS or MODIS NDVI data were considered. We tentatively attribute this underestimation to an increased ratio of grass biomass to forb biomass, which could delay the advancement of NDVI development but not affect that of field‐measured biomass development. Our results suggest that satellite‐derived NDVI data may miss critical responses of vegetation growth to global climate change, potentially due to long‐term shifts in plant community composition.

Identification and antimicrobial properties of a new alkaloid produced by marine-derived Verrucosispora sp. FIM06-0036 - Ming-Hong Chen; Yun-Yang Lian; Dong-Sheng Fang; Li Chen; Jia Jia; Wen-Long Zhang; Ru Lin; Yang Xie; Hong-Kai Bi; Hong Jiang (Natural Product Research, 2021)

New titanite U–Pb and molybdenite Re–Os ages for a hydrothermal vein-type Cu deposit in the Lanping Basin, Yunnan, SW China: constraints on regional metallogeny and implications for exploration - Juan Li; Lei-Luo Xu; Xian-Wu Bi; Yong-Yong Tang; Xiang-Yuan Sheng; Hai-Jun Yu; Gong Liu; Rui Ma (Mineralium Deposita, 2021)

Long-Term Scheduling of Cascade Reservoirs Considering Inflow Forecasting Uncertainty Based on a Disaggregation Model - Xiaoling Ding; Xiaocong Mo; Jianzhong Zhou; Sheng Bi; Benjun Jia; Xiang Liao (Water Resources Management, 2021)

Climate-Driven Range Shifts of Brown Seaweed Sargassum horneri in the Northwest Pacific - Jing-Jing Li; Sheng-Hui Huang; Zheng-Yi Liu; Yuan-Xin Bi (Frontiers in Marine Science, 2020)

Microseismic Monitoring to Characterize Structure-Type Rockbursts: A Case Study of a TBM-Excavated Tunnel - Quan-Sheng Liu; Jian Wu; Xiao-Ping Zhang; Lie-Xian Tang; Chen Bi; Wei-Wei Li; Jin-Lin Xu (Rock Mechanics and Rock Engineering, 2020)

Analysis of endophytic bacterial community diversity and metabolic correlation in Cinnamomum camphora - Guo-fang Zhang; Qiu-liang Huang; Xue-qin Bi; You-lin Liu; Zong-sheng Yuan (Archives of Microbiology, 2020)

Greenhouse gas mitigation potential under different rice-crop rotation systems: from site experiment to model evaluation - Xianxian Zhang; Junguo Bi; Huifeng Sun; Jining Zhang; Sheng Zhou (Clean Technologies and Environmental Policy, 2019)

Experimental Analysis on Dynamic Responses of an Electrical Platform for an Offshore Wind Farm under Earthquake Load - Zhen-Zhou Sun; Chun-Wei Bi; Sheng-Xiao Zhao; Guo-Hai Dong; Hua-Feng Yu (Journal of Marine Science and Engineering, 2019)
Offshore wind power is gradually developing to more open sea. Considering the economy of power transmission, it will be an inevitable choice to adopt the extra-large electrical platform. The offshore electrical platform is easily affected by sudden extreme loads such as earthquake and high current loads. With a large volume of electrical equipment arranged on the deck, the offshore electrical platform is characterized as a top-heavy structure in the offshore wind farm. The dynamic effect of the structure will aggravate the vibration problem of the structure. In this paper, a physical model test was carried out to study the dynamic characteristics of the electrical platform of a 10,000-ton offshore converter station under seismic load. The acceleration response, displacement response and stress response of the offshore electrical platform under the typical direction of seismic action were obtained. The effect of the dry–wet environment, mode of seismic excitation, whipping effect and weak positions of electrical platform structure were analyzed. It was determined that the average damping ratio of the first-order mode of the electrical platform was 5.73% and 8.68% with and without water, respectively. The bidirectional seismic excitation was more dangerous to the structure than unidirectional excitation. The peak acceleration along the height of the platform showed a typical whipping effect.

Asperpyrone F, a new dimeric naphtho- γ -pyrone from the edible fungus Pleurotus ostreatus - Xu Cai; Yang Yu; Qian Li; Ben-Ke Chen; Yun Huang; Xian-Wei Zou; Jin-Tian Tang; Bi-Sheng Huang (Natural Product Research, 2019)

Two new noroleanane-type triterpenoid saponins from the stems of Stauntonia chinensis - Tong-Tong Feng; Hui-Zheng Fu; Yi-Sheng Yang; Zhi-Qiang Zhou; Mian Dai; Hong-Yu Bi; Dong Wang (Natural Product Research, 2019)

Enzymatic transformation of ginsenosides Re, Rg1, and Rf to ginsenosides Rg2 and aglycon PPT by using β-glucosidase from Thermotoga neapolitana - Yun-Feng Bi; Xi-Zhu Wang; Shan Jiang; Jing-Sheng Liu; Ming-Zhu Zheng; Ping Chen (Biotechnology Letters, 2019)

A terrain openness index for the extraction of karst Fenglin and Fengcong landform units from DEMs - Xin Meng; Li-yang Xiong; Xian-wu Yang; Bi-sheng Yang; Guo-an Tang (Journal of Mountain Science, 2018)

Effects of short-term inflammatory and/or hypoxic pretreatments on periodontal ligament stem cells: in vitro and in vivo studies - Yang Yu; Chun-Sheng Bi; Rui-Xin Wu; Yuan Yin; Xi-Yu Zhang; Ping-Heng Lan; Fa-Ming Chen (Cell and Tissue Research, 2016)

Measurement of aerosol effective density by single particle mass spectrometry - GuoHua Zhang; XinHui Bi; BingXue Han; Ning Qiu; ShouHui Dai; XinMing Wang; GuoYing Sheng; JiaMo Fu (Science China Earth Sciences, 2016)

TG-interacting factor mediates arsenic-induced malignant transformation of keratinocytes via c-Src/EGFR/AKT/FOXO3A and redox signalings - Zi-Miao Liu; Hong-Yu Tseng; Bi-Wen Yeh; Wen-Jeng Wu; Huei-Sheng Huang (Archives of Toxicology, 2015)

Nontuberculous mycobacterial osteomyelitis - Sheng Bi; Fei-Shu Hu; Hai-Ying Yu; Kai-Jin Xu; Bei-Wen Zheng; Zhong-Kang Ji; Jun-Jie Li; Mei Deng; Hai-Yang Hu; Ji-Fang Sheng (Infectious Diseases, 2015)

Myosin II regulates actin rearrangement-related structural synaptic plasticity during conditioned taste aversion memory extinction - Ai-Ling Bi; Yue Wang; Shuang Zhang; Bo-Qin Li; Zong-Peng Sun; Hong-Sheng Bi; Zhe-Yu Chen (Brain Structure and Function, 2015)

Developing microsatellite markers for Geodorum eulophioides (Orchidaceae) and cross-species amplification in two sympatric, congeneric species - Ting Ying; Qi-Fang Geng; Dan-Bi Wang; Hong Liu; Jing Xu; Zi-Bing Zhang; Zhong-Sheng Wang; Yi-Bo Luo (Conservation Genetics Resources, 2014)

Inverse associations of outdoor activity and vitamin D intake with the risk of Parkinson’s disease - Dan Zhu; Gui-you Liu; Zheng Lv; Shi-rong Wen; Sheng Bi; Wei-zhi Wang (Journal of Zhejiang University-SCIENCE B, 2014)

Characteristics of Malignant Tumors in 230 Husband–Wife Pairs - Ju Liu; Zhijian Xu; Kai Zhang; Huai Li; Sheng Chang; Xiaofeng Bi; Min Dai (Cell Biochemistry and Biophysics, 2014)

Estimation of tropical cyclone parameters and wind fields from SAR images - Xuan Zhou; XiaoFeng Yang; ZiWei Li; Yang Yu; HaiBo Bi; Sheng Ma; XiaoFeng Li (Science China Earth Sciences, 2013)

Enterocin T, a novel class IIa bacteriocin produced by Enterococcus sp. 812 - Yi-sheng Chen; Chi-rong Yu; Si-hua Ji; Min-shiuan Liou; Kun-hon Leong; Shwu-fen Pan; Hui-chung Wu; Yu-hsuan Lin; Bi Yu; Fujitoshi Yanagida (Archives of Microbiology, 2013)

Characteristics, loss and gain of atmospheric carbonyl compounds in winters of 2008–2010 in Pearl River Delta region, China - Yonglin Liu; Xinhui Bi; L. Y. Chan; Sheng Wen; Xinming Wang; Guoying Sheng; Jiamo Fu (Journal of Atmospheric Chemistry, 2013)

Exon 47 skipping of fibrillin-1 leads preferentially to cardiovascular defects in patients with thoracic aortic aneurysms and dissections - Wen-Jing Wang; Peili Han; Jun Zheng; Fang-Yuan Hu; Yun Zhu; Jin-Sheng Xie; Jian Guo; Zhe Zhang; Jie Dong; Gu-Yan Zheng; Huiqing Cao; Tian-Shu Liu; et al. (Journal of Molecular Medicine, 2013)

A molecular mechanism underlying ovarian dysfunction of polycystic ovary syndrome: hyperandrogenism induces epigenetic alterations in the granulosa cells - Fan Qu; Fang-Fang Wang; Rong Yin; Guo-Lian Ding; Mohamed El-prince; Qian Gao; Bi-Wei Shi; Hui-Hui Pan; Yi-Ting Huang; Min Jin; Peter C. K. Leung; Jian-Zhong Sheng; et al. (Journal of Molecular Medicine, 2012)

bla KPC and rmtB on a single plasmid in Enterobacter amnigenus and Klebsiella pneumoniae isolates from the same patient - J.-F. Sheng; J.-J. Li; S. Tu; Z.-K. Sheng; S. Bi; M.-H. Zhu; X.-M. Shen; L.-J. Li (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Serotonin accumulation in transgenic rice by over-expressing tryptophan decarboxlyase results in a dark brown phenotype and stunted growth - Parawee Kanjanaphachoat; Bi-Yin Wei; Shuen-Fang Lo; I-Wen Wang; Chang-Sheng Wang; Su-May Yu; Ming-Liang Yen; Sheng-Hsien Chiu; Chien-Chen Lai; Liang-Jwu Chen (Plant Molecular Biology, 2012)

PTEN inhibits proliferation and functions of hypertrophic scar fibroblasts - Liang Guo; Liang Chen; Sheng Bi; Linlin Chai; Zengxiang Wang; Chuan Cao; Ling Tao; Shirong Li (Molecular and Cellular Biochemistry, 2012)

Donor-Acceptor Compound Based on Rhodanineacetic Acid-Pyrene Derivative: Red-Light Emitting Fluorescent Organic Nanoparticles - Bo Zhang; Wei Diao; Chun Bi; Jian Sun; Guoxia Han; Yi Shi; Li Sheng; Gui Yin; Lin Pu (Journal of Fluorescence, 2012)

Chemical composition of precipitation and its sources in Hangzhou, China - Hong Xu; Xiao-Hui Bi; Yin-Chang Feng; Feng-Mei Lin; Li Jiao; Sheng-Mao Hong; Wen-Gao Liu; Xiao-Yong Zhang (Environmental Monitoring and Assessment, 2011)

Phenotypic and Genotypic Characterization Vibrio cholerae O139 of Clinical and Aquatic Isolates in China - Bai-sheng Li; Hai-ling Tan; Duo-chun Wang; Xiao-ling Deng; Jing-diao Chen; Hao-jie Zhong; Bi-xia Ke; Chang-wen Ke; Biao Kan (Current Microbiology, 2011)

Isolation and Characterization of Putative Acetyl-CoA Carboxylases in Arachis hypogaea L. - Meng-Jun Li; Han Xia; Chuan-Zhi Zhao; Ai-Qin Li; Chang-Sheng Li; Yu-Ping Bi; Shu-Bo Wan; Xing-Jun Wang (Plant Molecular Biology Reporter, 2010)

Cloning and sequence analysis of putative type II fatty acid synthase genes from Arachis hypogaea L. - Meng-Jun Li; Ai-Qin Li; Han Xia; Chuan-Zhi Zhao; Chang-Sheng Li; Shu-Bo Wan; Yu-Ping Bi; Xing-Jun Wang (Journal of Biosciences, 2009)

Deletion analysis of SMN1 and NAIP genes in southern Chinese children with spinal muscular atrophy - Yu-hua Liang; Xiao-ling Chen; Zhong-sheng Yu; Chun-yue Chen; Sheng Bi; Lian-gen Mao; Bo-lin Zhou; Xian-ning Zhang (Journal of Zhejiang University-SCIENCE B, 2009)

Distribution, Source Apportionment, and Transport of PAHs in Sediments from the Pearl River Delta and the Northern South China Sea - Xiao-Jun Luo; She-Jun Chen; Bi-Xian Mai; Guo-Ying Sheng; Jia-Mo Fu; Eddy Y. Zeng (Archives of Environmental Contamination and Toxicology, 2008)

Chemical Composition and Sources of PM10 and PM2.5 Aerosols in Guangzhou, China - Xinhua Wang; Xinhui Bi; Guoying Sheng; Jiamo Fu (Environmental Monitoring and Assessment, 2006)

Seasonal Variation of the Particle Size Distribution of n-Alkanes and Polycyclic Aromatic Hydrocarbons (PAHs) in Urban Aerosol of Guangzhou, China - X. L. Tang; X. H. Bi; G. Y. Sheng; J. H. Tan; J. M. FU (Environmental Monitoring and Assessment, 2006)

Relationships among multiple trace elements in coastal Casuarina equisetifolia ecosystems on Hainan Island, South China - Qiang Liu; Hua Bi; Lan Hung; Shaolin Peng; Chengde Sheng (Environmental Geochemistry and Health, 2006)

Construction of a genetic linkage map and QTL analysis of fiber-related traits in upland cotton (Gossypium hirsutum L.) - Zheng-Sheng Zhang; Yue-Hua Xiao; Ming Luo; Xian-Bi Li; Xiao-Ying Luo; Lei Hou; De-Mou Li; Yan Pei (Euphytica, 2005)

Effects of soy sauce koji and lactic acid bacteria on the fermentation of fish sauce from freshwater silver carp Hypophthalmichthys molitrix - Motoharu UCHIDA; Jie OU; Bi-Wen CHEN; Chun-Hong YUAN; Xur-Hua ZHANG; Shun-Sheng CHEN; Yasuhiro FUNATSU; Ken-Ichi KAWASAKI; Masataka SATOMI; Yutaka FUKUDA (Fisheries Science, 2005)